Impact of partially treated sewage effluent on the water quality of recipient Epie Creek Niger Delta, Nigeria using Malaysian Water Quality Index (WQI) - A Rim-Rukeh; LE Agbozu (Journal of Applied Sciences and Environmental Management)
Impact of partially treated sewage effluent on the water quality of recipient Epie Creek in the Niger Delta area of Nigeria was investigated  experimentally by analysing the physico-chemical and biological characteristics of the surface water samples collected at four (4) sampling stations: at the effluent discharge point (fall out) (SS2), 500 m upstream (SS1), 500m downstream (SS3) and 1000m (SS4) downstream respectively from the point of discharge. Sampling was carried out weekly between June 2009 and May 2010 (48 weeks). Measured parameters of the water samples and the corresponding results are: pH (5.60 – 6.80), turbidity (21.5 – 34.7 NTU), electrical conductivity (34.7 – 82.1 ìS/cm), biochemical oxygen demand (BOD) (12.4 -36.7 mg/l), chemical oxygen demand (COD) (17.3 – 53.2 mg/l), total suspended solids (TSS) (17.70- 45.8 mg/l), dissolved oxygen (DO) (3.73 – 5.20 mg/l), total dissolved solids (TDS) (57.3 – 187.0 mg/l), total phosphate (0.73 – 1.73 mg/l), ammoniacal nitrogen (AN) (4.10 – 5.0 mg/l) and total fecal coliform count (TFCC) (2,120 – 20,800 cfu/ml). The water quality at each of the sampling points was also assessed using Malaysian Water Quality Index (WQI) and results show that, the water quality of Epie Creek defined at the sampling stations belongs to Class IV with values that ranged between 31.0 and 51.9. Empirically, the water quality can be described as fairly polluted. This means that the water quality across the sampling points is poor indicating that most parameters have deteriorated.